Posture control and balance for quality of walking in rehabilitation - Li, Lei (2016)
Impairments such as spinal cord injury (SCI), stroke or aging can cause deficits in motor control and muscle weakness. The deficits will affect walking ability and the individuals’ ability to live independently. Rehabilitation process can help the impaired individuals improve their walking ability by large volume of repetitive walking. Nevertheless, many subjects still require lower-limb assistive devices such as lower-limb orthosis and lower-limb robotic exoskeleton to compensate for unrecoverable functions. However, most current lower-limb assistive devices do not provide adequate assistance that is needed to maintain postural balance.